The Image of China at the Opening Ceremony of Beijing 2022 Winter Olympics Based on Multimodal Analysis - Cai, Tianrun; Chen, Yipei; Mao, Jiarui; Chen, Jiahua; Chen, Ruihan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aims to promote the communication and cognition of China’s national image in the world by investigating the utilization of multimodal metaphors at the Opening Ceremony of Beijing 2022 Winter Olympics and the national image that the multimodal metaphors indicate. This paper utilizes the multimodal corpus that contains multiple media types such as texts, audio and images to conduct multimodal analysis and to investigate how to achieve effective transmission from three perspectives (the cognitive, emotional, and behavioral aspects). Further, in order to confirm the effectiveness of this transmission, data analysis is carried out based on the comments about the opening ceremony of Beijing Winter Olympics on YouTube. Based on the results of data analysis and discussion, the study concludes four images of China from the Opening Ceremony: a major country with firm cultural self-confidence, with the endeavor to build a human community with a shared future, with advanced science and technology, and with persistence of sustainable development